2021
DOI: 10.1101/2021.06.14.448336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacteriophage T4 Vaccine Platform for Next-generation Influenza Vaccine Development

Abstract: Developing influenza vaccines that protect against a broad range of viruses is a public health priority, and several conserved viral proteins or domains have been identified as promising targets for such vaccine development. However, none of the targets is immunogenic, and vaccine platforms that can incorporate multiple antigens with enhanced immunogenicity are desperately needed. In this study, we provided proof-of-concept for the development of next-generation influenza vaccine using T4 phage virus-like part… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Microbiome analyses showed no significant changes in the microbiome diversity in mice vaccinated with the T4-CoV-2 vaccine. In human clinical trials and hundreds of T4 phage vaccine immunizations over the years involving mice, rats, rabbits, and macaque animal models and diverse antigens such as anthrax, plague, and HIV did not identify any significant side effects (Li et al, 2021; Rao et al, 2011b; Tao et al, 2013; Tao et al, 2018a; Zhu et al, 2019). Furthermore, the T4 phage is one of the most stable virus scaffolds known (Jończyk et al, 2011) and our stability studies showed that the T4-CoV-2 vaccine was completely stable at ambient temperature for at least 10-weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiome analyses showed no significant changes in the microbiome diversity in mice vaccinated with the T4-CoV-2 vaccine. In human clinical trials and hundreds of T4 phage vaccine immunizations over the years involving mice, rats, rabbits, and macaque animal models and diverse antigens such as anthrax, plague, and HIV did not identify any significant side effects (Li et al, 2021; Rao et al, 2011b; Tao et al, 2013; Tao et al, 2018a; Zhu et al, 2019). Furthermore, the T4 phage is one of the most stable virus scaffolds known (Jończyk et al, 2011) and our stability studies showed that the T4-CoV-2 vaccine was completely stable at ambient temperature for at least 10-weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we used an in vitro assembly system to display antigen-Soc fusion proteins on T4 capsid by mixing the fusion proteins with Hoc -Soc -T4 phages. [15][16][17]24] The highly efficient phage genome editing technology recently developed using CRISPR-Cas allowed us to display foreign proteins on T4 capsid in vivo by inserting the coding sequence into T4 genome in-frame at the C terminus of Soc gene. [19,21,25] During the propagation of recombinant T4 phages in E. coli, expressed Soc-antigen proteins are expected to assemble on T4 capsids to form antigendecorated nanoparticles.…”
Section: Assembly Of 3m2e Decorated T4 Nanoparticles In Vivo Using Ge...mentioning
confidence: 99%
“…[15,16,18,19] The generated nanoparticles without any adjuvant induced robust systemic immune responses and provided complete protections against challenge in different animal models, indicating the potent intrinsic adjuvant activity of phage T4. [15,16] Recent studies indicated that phage T4 can be enriched in mucus layer on mucosal surfaces of human and all other tested animals through binding to mucin glycoproteins, which increases the chance to interact with their bacterial hosts. [20] The mucoadhesive feature of phages along with their intrinsic adjuvant activities could be a defense mechanism of metazoan against invasive bacteria.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations